An Apple iPad a Day Brings the Doctor to You: Virtual Family-Centered Rounds in a Pediatric Intensive Care Unit - Solt, Shannon A.; Stolfi, Danielle; Ritter, Victor Silva; Kihlstrom, Margaret (Journal of Pediatric Intensive Care, 2022)
The purpose of this study was to evaluate if virtual family-centered rounds (VFCR) in a pediatric intensive care unit (PICU) would improve communication without significantly increasing rounding time. An observational study was conducted recording rounding times of patient encounters. Then, in March 2019, English-speaking families were offered the opportunity to round virtually. Families were required to have access to a device with video conferencing capabilities and were video conferenced into rounds via Skype. Participants completed an online satisfaction survey. Rounding times were not significantly different for families present on rounds compared with not present (10 minutes 49 seconds vs. 9 minutes 42 seconds; p = 0.2). The average length of VFCR was 11 minutes 19 seconds; this was not statistically significant when compared with no family present (p = 0.5) or family present (p = 0.8). Majority of nurses (85%) and over half of physicians (53%) felt that VFCR were very helpful. One hundred percent of families and the majority of physicians and nurses felt that it positively impacted family communication. All families felt that VFCR improved their understanding of their child's medical condition, and the majority felt it improved their understanding of the treatment plan. VFCR positively impacts the communication in the PICU and can be used for families unable to be present for rounds without significantly increasing rounding times.
Keywords: pediatrics; critical care; video conferencing; family-centered rounds; communication